Prediction of pyramidal tract side effect threshold by intra-operative electromyography in subthalamic nucleus deep brain stimulation for patients with Parkinson's disease under general anaesthesia - Leung, Lok Wa Laura; Lau, Ka Yee Claire; Kan, Kwok Yee Patricia; Ng, Yikjin Amelia; Chan, Man Chung Matthew; Ng, Chi Ping Stephanie; Cheung, Wing Lok; Hui, Ka Ho Victor; Chan, Yuen Chung David; Zhu, Xian Lun; Chan, Tat Ming Danny; Poon, Wai Sang (Frontiers in Surgery, 2024)
IntroductionIn DBS for patients with PD, STN is the most common DBS target with the sweet point located dorsal ipsilaterally adjacent to the pyramidal tract. During awake DBS lead implantation, macrostimulation is performed to test the clinical effects and side effects especially the pyramidal tract side effect (PTSE) threshold. A too low PTSE threshold will compromise the therapeutic stimulation window. When DBS lead implantation is performed under general anaesthesia (GA), there is a lack of real time feedback regarding the PTSE. In this study, we evaluated the macrostimulation-induced PTSE by electromyography (EMG) during DBS surgery under GA. Our aim is to investigate the prediction of post-operative programming PTSE threshold using EMG-based PTSE threshold, and its potential application to guide intra-operative lead implantation.Methods44 patients with advanced PD received STN DBS under GA were studied. Intra-operative macrostimulation via EMG was assessed from the contralateral upper limb. EMG signal activation was defined as the amplitude doubling or greater than the base line. In the first programming session at one month post-operation, the PTSE threshold was documented. All patients were followed up for one year to assess clinical outcome.ResultsAll 44 cases (88 sides) demonstrated activations of limb EMG via increasing amplitude of macrostimulation the contralateral STN under GA. Revision tracts were explored in 7 patients due to a low EMG activation threshold (<= 2.5 mA). The mean intraoperative EMG-based PTSE threshold was 4.3 mA (SD 1.2 mA, Range 2.0–8.0 mA), programming PTSE threshold was 3.7 mA (SD 0.8 mA, Range 2.0–6.5 mA). Linear regression showed that EMG-based PTSE threshold was a statistically significant predictor variable for the programming PTSE threshold (p value <0.001). At one year, the mean improvement of UPDRS Part III score at medication-off/DBS-on was 54.0% (SD 12.7%) and the levodopa equivalent dose (LED) reduction was 59.5% (SD 23.5%).ConclusionDuring STN DBS lead implantation under GA, PTSE threshold can be tested by EMG through macrostimulation. It can provide real-time information on the laterality of the trajectory and serves as reference to guide intra-operative DBS lead placement.